Dimension Effect on P-y Model Used for Design of Laterally Loaded Piles. (2016) - Yang, Min; Ge, Bin; Li, Weichao; Zhu, Bitang
Abstract: Piles are usually used as mooring or berthing dolphins in harbor to resist lateral loads mainly induced from ships' impact, and as foundations for bridges and offshore structures (e.g. offshore wind turbines) to resist lateral and axial loads. During the design, the response of these piles to lateral loading should be analyzed, and in some circumstances, the lateral response governs the piles' design. P-y curve method is the most popular approach and also is recommended by the offshore design standards/guidelines, such as American Petroleum Institute and Det Norske Veritas. However, the reliability of current P-y models is questionable when these models are employed to design a pile with dimensions beyond their originated field tests. In this study, firstly, field lateral loading tests on a rigid pile and a number of finite element analyses are comparably investigated. Then, a detailed evaluation of current P-y models is performed and discussed. Finally, a refined design guideline is presented for laterally loaded piles with a wider range of dimensions.